Políticas educacionais e escolas rurais no Paraná : 1930-2005 - Bareiro, Edson (2007)
This paper treats of the rural schools in Paraná, as they are structured and your situation along last century and which your tendency now. Presents a retrospective one historical on the public politics and the discussions in each historical period on the theme rural education in Brazil and in the State of Paraná. He/she/you shows that in Brazil the politics gone back to the rural schools they were always harnessed to the crises by the which it passed the field in the country, be the rural exodus, the modernization of the agriculture and the pressure of the Social Movements in search of the Agrarian Reform. In the State of Paraná the rural schools went being implanted the measure that the pioneering fronts of colonization moved forward in the North and Southwest area. In the other areas of older colonization there were already countless schools, starting from the modernization of the agriculture, it happens besides the change of agricultural culture, an alteration in the structure of the country in the State and it provokes an intense rural exodus inverting the situation of home of the population that was rural previous to that processo The rural schools go by an extinction process that arrives at our days, the initiatives to offer the population that continues in the field paranaense the access the education are at the transport schools for the city and in the nucleation of old isolated rural schools, besides initiatives of ONGs and Social Movements .